INFLUENCE OF PHOSPHORUS-RETARDANT ON FLAMMABILITY AND ON PHYSICAL AND MECHANICAL PROPERTIES OF EPOXY COMPOUND - Trachevskyi, Vyacheslav; Molozovenko, Katerina; Zinchenko, Marina (Proceedings of National Aviation University (archive), 2012)
Presents the influence of flame retardant on the flammability of polymeric materials. The influence of phosphorus compounds on flammability and physical and mechanical properties of epoxy polymers. Experimentally shows the possible methods of reducing their combustibility without changing the physical and mechanical characteristics.